PELATIHAN PUPUK ORGANIK CAIR (POC) DARI URINE SAPI DI DESA JOHUNUT KECAMATAN PARANGGUPITO KABUPATEN WONOGIRI - Ikhsan Hidayat Suratman; Vinka Widia Pamela; Airlangga Hamdan Pratama; Mochamad Akbar Raihan; Kusumaningdyah Nurul Handayani (COVIT (Community Service of Health), 2023)
This article examines the extension of liquid organic fertilizer from cow urine in farmer groups in Johunut Village. The majority of Johunut Village community works as farmers and breeders. However, the people of Johunut Village have not used cow urine even though they have many benefits in cow urine such as, the price is relatively cheap, easy to obtain, and contained nutrients needed by plants. This socialization activity has the aim to increase public knowledge about the potential of cow urine as liquid fertilizer. Meanwhile, this article is useful for fostering farmers' independence so as not to depend on chemical fertilizers and subsidies. The socialization activity regarding the making of liquid organic fertilizer from cow urine was held on February 8, 2023 consisting of two sessions, the first was a material exposure session and the second was the practice session for making liquid organic fertilizer from cow urine. The socialization activities carried out showed the enthusiasm of relatively high participants. However, in the sustainability of making liquid organic fertilizer from livestock urine by residents constrained by unodified livestock pens to accommodate cow urine. Keywords: Fertilizer, Organic, Urine